A novel low-frequency broadband piezoelectric energy harvester combined with a negative stiffness vibration isolator. (April 2019) - Cao, Dongxing; Guo, Xiangying; Hu, Wenhua
The transformation of waste vibration energy into low-power electricity has been intensely researched over the last decade to enable self-sustained wireless electronic components. Many kinds of nonlinear oscillators have been explored by several research groups in an effort to enhance the frequency bandwidth of operation. The negative stiffness vibration isolator, as a kind of passive vibration isolator, has undergone extensive investigation because of its low-frequency isolator characteristics. In this article, a novel broadband piezoelectric vibration energy harvester, which can be used for low-frequency ambient mechanical energy harvesting, is designed, and its dynamic responses are analyzed based on the advantage of the negative stiffness vibration isolator. The multi-scale perturbation method is applied to solve the electromechanical equations of the piezoelectric vibration energy harvester and obtain approximate analytical solutions. Solutions based on the analytical method and numerical simulations reveal the characteristics of significant broadband performance. The effects of the various system parameters on the frequency responses and output voltage of the piezoelectric vibration energy harvester system are investigated in detail, and the vibration isolation ability is verified by experimental measurements. It was concluded that the proposed piezoelectric vibration energy harvester achieved broadband vibration energy harvesting in the low-frequency vibration range.